Analisis Graph Clustering Terhadap User Behavior Di Official Account Facebook Universitas Bina Darma Palembang - Ayu Gahardina; Ilman Zuhri Yadi (Journal of Computer and Information Systems Ampera, 2020)
At a time when the times are increasing, it cannot be denied that almost some people use social media as a means of communication. Not only is it a means of communication, even social media is a place to show their habits. Without realizing it, the more information that is spread on social media regarding self-information, it will make information that can benefit others. User Behavior Analytics as defined by Gartner is a cybersecurity process of detection of insider threats, targeted attacks and financial fraud. The UBA solution looks at patterns of human behaviour and then applies algorithms and statistical analysis to detect meaningful anomalies of those patterns. Gephi is an open-source network visualization platform that can be used to analyze various cases using graph visualization. One of these analyzes can be done by using data that has been scraped from social media, Facebook, social media, Bina Darma University to get data visualization of the cases being tested. From these results, the graph clustering process is carried out in Gephi to obtain data clusters. The results will then be analyzed and identified so that they can become material for information about social media user behaviour.